PEMANFAATAN HASIL PELATIHAN KETERAMPILAN DAN PERAN PENDAMPING DALAM MENINGKATKAN KEMANDIRIAN USAHA (Studi Pada Program Desa Vokasi di Desa Cisaat Kecamatan Ciater Kabupaten Subang Provinsi Jawa Barat) - MUHAMMAD ASRI (Jurnal Pendidikan Luar Sekolah, 2016)
Vocational village community empowerment program held in the village Cisaat, an effort to improve the quality of human resources in the village pembagunan sabagai business independence. To realize the independence of the business can be done through the village of vocational programs. One of the institutions that menyelaggarakan Village vocational program in order to improve the business independence of the PP-PAUDNI Ragional I Bandung. In the process, kemandiran businesses affected by the utilization of skills training. The result showed that the utilization of skills training by village residents Vocational very good, very helpful companion role and facilitate citizens Vocational Village business group in developing its business, the impact of the utilization of skills training for business autonomy Vocational Village residents group